Tính nhanh 5/11×7/6+7/6×6/11+5/6
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
(6 : 3/5 - 7/6 x 6/7 ) : ( 21/5 x 10/11 + 57/11 )
=9:9
=1
\(a,A=\dfrac{\dfrac{5}{4}+\dfrac{5}{5}+\dfrac{5}{7}-\dfrac{5}{11}}{\dfrac{10}{4}+\dfrac{10}{5}+\dfrac{10}{7}-\dfrac{10}{11}}\\ =\dfrac{5.\left(\dfrac{1}{4}+\dfrac{1}{5}+\dfrac{1}{7}-\dfrac{1}{11}\right)}{10.\left(\dfrac{1}{4}+\dfrac{1}{5}+\dfrac{1}{7}-\dfrac{1}{11}\right)}\\ =\dfrac{5}{10}\\ =\dfrac{1}{2}\)
Vậy \(A=\dfrac{1}{2}\)
\(b,B=\dfrac{2+\dfrac{6}{5}-\dfrac{6}{7}-\dfrac{6}{11}}{\dfrac{2}{3}+\dfrac{2}{5}-\dfrac{2}{7}-\dfrac{2}{11}}\\ =\dfrac{3.\left(\dfrac{2}{3}+\dfrac{2}{5}-\dfrac{2}{7}-\dfrac{2}{11}\right)}{\dfrac{2}{3}+\dfrac{2}{5}-\dfrac{2}{7}-\dfrac{2}{11}}\\ =3\)
Vậy \(B=3\)
\(A,\dfrac{7}{11}+\dfrac{5}{6}-\dfrac{-4}{11}-\dfrac{1}{6}\)
\(= (\dfrac{7}{11}+\dfrac{-4}{11})-(\dfrac{5}{6}-\dfrac{1}{6})\)
\(=\dfrac{3}{11}-\dfrac{2}{3}\)
\(= \dfrac{9}{33}-\dfrac{22}{33}\)
\(= \dfrac{-13}{33}\)
\(B,\dfrac{5}{9}.\dfrac{7}{3}+\dfrac{5}{9}.\dfrac{9}{13}-\dfrac{5}{9}:\dfrac{13}{5}\)
\(=(\dfrac{5}{9}.\dfrac{5}{9}:\dfrac{5}{9}).\dfrac{7}{3}+\dfrac{9}{13}-\dfrac{13}{5}\)
\(=(\dfrac{5}{9}.\dfrac{7}{3})+(\dfrac{9}{13}-\dfrac{13}{5})\)
\(=(\dfrac{5}{9}.\dfrac{21}{9})+(\dfrac{45}{65}-\dfrac{169}{65})\)
\(=\dfrac{35}{27}+\dfrac{-124}{65}\)
\(=\dfrac{2275}{1755}+\dfrac{-3348}{1755}\)
\(=\dfrac{-1073}{1755}\)
Mình nghĩ đề là : 2/8 sẽ hay hơn.
\(B=\dfrac{5}{2}+\dfrac{6}{11}+\dfrac{2}{8}+\dfrac{7}{2}+\dfrac{6}{8}+\dfrac{5}{11}\)
\(=\left(\dfrac{5}{2}+\dfrac{7}{2}\right)+\left(\dfrac{6}{11}+\dfrac{5}{11}\right)+\left(\dfrac{2}{8}+\dfrac{6}{8}\right)\)
\(=6+1+1=8\)
\(=\dfrac{5\left(5+2\right)}{11.7}+\dfrac{6}{11}=\dfrac{5}{11}+\dfrac{6}{11}=1\)
Ta có:
= 5/11 .( 5/7+ 2/7 ) + 6/11
= 5/11 . 1 + 6/11
= 11/ 11
= 1
#học tốt ạ :3
1+2+3+4+5+6+7+8+9+10+11+12+13-1-2-3-4-5-6-7-8-9-10-11-12
=(1-1)+(2-2)+(3-3)+(4-4)+(5-5)+(6-6)+(7-7)+(8-8)+(9-9)+(10-10)+(11-11)+(12-12)+13
= 0 + 0 + 0 + 0 + 0 + 0 + 0 + 0 + 0 + 0 + 0 + 0 + 13
= 13
1 + 2 + 3 + 4 + 5 + 6 + 7 + 8 + 9 + 10 + 11 + 12 + 13 - 1 - 2 - 3 - 4 - 5 - 6 - 7- 8 - 9 - 10
= (1+12) + (2+11) + (3+10) + ( 4+9) + (5+8) + (6+7) + 13 - (1+11) - ( 2+10) - ( 3+9) - (4+8) - (5+7) + 6 + 12
= 13 * 7 - 12 * 6 + 6
= 13
Ai k mk mk k lại
`#25080409`
\(\dfrac{6}{11}\times\dfrac{3}{7}+\dfrac{3}{7}\times\dfrac{5}{11}?\)
`=`\(\left(\dfrac{6}{11}+\dfrac{5}{11}\right)\times\dfrac{3}{7}\)
`=`\(\dfrac{11}{11}\times\dfrac{3}{7}=1\times\dfrac{3}{7}=\dfrac{3}{7}\)
`5/11 \times 7/6 + 7/6 \times 6/11 + 5/6`
`= 7/6 \times (5/11 + 6/11) + 5/6`
`= 7/6 \times 11/11 + 5/6`
`= 7/6 \times 1 + 5/6`
`= 7/6 + 5/6`
`= 12/6`
`= 2`
`5/11 \times 7/6 + 7/6 \times 6/11 + 5/6`
`= (5/11 + 6/11) \times 7/6 + 5/6`
`= 11/11 \times 7/6 + 5/6`
`= 1 \times 7/6 + 5/6`
`= 7/6 + 5/6`
`= 12/6`
`= 2`